Kecemasan Komunikasi Interpersonal antara Mahasiswa dan Dosen dalam Bimbingan Skripsi : (Studi Kasus: Mahasiswa Ilmu Komunikasi UMA Tahun Ajaran 2020/2021) - Mahardikapura Adriyanto Saragih; Taufik Wal Hidayat (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the interpersonal communication anxiety experienced by Communication Science students of Universitas Medan Area (UMA) from the 2020/2021 cohort during the thesis supervision process. Communication anxiety is one of the main barriers in academic interactions between students and their supervisors, directly affecting the effectiveness of supervision and thesis completion. This research employs a qualitative approach using a case study method, involving 12 purposively selected informants. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Braun & Clarke’s thematic analysis. The findings reveal various forms of anxiety, including nervousness when speaking, fear of criticism, confusion in expressing ideas, and avoidance of supervision, both in person and via digital media. The causes stem from internal factors (such as low self-confidence and academic perfectionism) and external factors (such as rigid communication styles of supervisors and limited access to communication). The impact of anxiety includes thesis delays, decreased motivation, and reduced academic productivity. Several adaptive strategies were identified, such as seeking peer support, preparing notes before consultations, and choosing appropriate times for communication. This study provides valuable insights for educational institutions to foster a more supportive and responsive supervision environment that addresses students' psychological needs.